2001
DOI: 10.1091/mbc.12.10.2975
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Receptors Promote β1 Integrin Function through Interactions with Integrin α3β1

Abstract: The urokinase receptor (uPAR) is linked to cellular migration through its capacity to promote pericellular proteolysis, regulate integrin function, and mediate cell signaling in response to urokinase (uPA) binding. The mechanisms for these activities remain incompletely defined, although uPAR was recently identified as a cis-acting ligand for the ␤2 integrin CD11b/CD18 (Mac-1). Here we show that a major ␤1 integrin partner for uPAR/uPA signaling is ␣3. In uPAR-transfected 293 cells uPAR complexed (Ͼ90%) with ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
269
3
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(287 citation statements)
references
References 50 publications
11
269
3
4
Order By: Relevance
“…43 uPA has been shown to break down various components of extracellular matrix, including laminin, fibronectin and collagen through the generation of plasmin. 16 In general, tumor cells of several human malignancies express detectable cell surface-associated uPA and plasmin activity, and this positively correlates with their invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…43 uPA has been shown to break down various components of extracellular matrix, including laminin, fibronectin and collagen through the generation of plasmin. 16 In general, tumor cells of several human malignancies express detectable cell surface-associated uPA and plasmin activity, and this positively correlates with their invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Available data in cultured cancer cells, however, indicate that uPAR overexpression activates cell proliferation by interacting with integrins and with growth factor receptor tyrosine kinases like the EGF and the PDGF receptors (Liu et al, 2002;Kiyan et al, 2005). However, peptide a325 that dissociates uPAR-a3b1 and -a5b1 complexes (Wei et al, 2001;Mazzieri et al, 2006) had no effect on wt MEFs growth rate or ERK activation (data not shown). It is known that overexpression of uPAR in Hep3 cells, for example, modifies the response of the EGF-R to EGF, so that EGF-R was activated in the absence of EGF (Liu et al, 2002).…”
Section: )mentioning
confidence: 93%
“…Previously, we demonstrated this integrin-uPA interaction in tumor-associated macrophages of breast cancer (12). Furthermore, it was demonstrated that integrins (·3ß1) are associated with uPAR in MDA-MB-231 breast cancer cells (13). Since uPAR lacks transmembrane and intracytoplasmic domain for uPA-induced signal tranduction, uPAR-integrin collaboration is essential.…”
Section: Introductionmentioning
confidence: 90%
“…Whereas, for cell counting, cells were trypsinized and counted using a hemocytometer. It was demonstrated by Wei et al that ·3ß1 integrins are associated with uPAR in MDA-MB-231 breast cancer cells (13). uPAR-dependent functions are blocked by antibodies to ·3 (P1B5).…”
Section: Facs Analysis (S-phase Analysis)mentioning
confidence: 99%